UPAYA MENINGKATKAN KOMUNIKASI MATEMATIS SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) DALAM PEMBELAJARAN MATEMATIKA PADA SISWA KELAS VIII C SMP NEGERI 14 MADIUN - Bebe, Marlince Pati (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2019)
There were two kinds of student,s mathematical communication. They  were oral communication and written communiction. Oral communication meant that a student could communicate his ideas, sysbols, and mathematics concepts by delivery utterances to other students or teacher. Written communication meant that a student could express his ideas by drawing tables, pictures, diagrams, and graphics, and translate real things, sucs as symbols and notations into pictures, graphics, tables, and diagram. The research aimed to increase the ability of the students of class VIII C of SMP Negeri 14 Madiun in mathematical communication n in learning coordinations system using TGT cooperative learning method. The research was a classroom Action Recearch and the subject of the research was the twenty-one students of class VIII C of SMP Negeri 14 Madiun. The research was conducted into two cycles and each cycle consisted of two meetings. The data were taken using test method, observasition method and taking note method on the site. The results of the research were as follows: (1) The average grade of the students written mathematical communication in the first cycle was 49,21 and it was 56,25 in the second cycle while the percentage of the class fulfilment in the first cycle was 36,84% and it was 61,11% in the second cycle. It showed that the ability of written mathematical communications was higher but it has not reached the indicator yet, (2) The total average of the student?s oral mathematical communication in the first cycle was 2,43 and it was categorized as modest., (3)The total average at learning activity the first cycle was 2,70 and it was categorized as good and it was 3,04 in the second cycle and it was categorized as good, and (4) TGT cooperative learning could increase student,s ability in the mathematical communication despite the result was not up maximum.